In vivo effect of beta-cyfluthrin on proteases in insecticide-resistant and susceptible strains of Tribolium castaneum (Herbst) beetles (University Journal of Zoology, Rajshahi University, 2007)
Key words: beta-cyfluthrinp; Tribolium castaneum; proteases; aminopeptidase; endopeptidase Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 7-12